The Mind and Heart of Resonance: The Role of Cognition and Emotions in Frame Effectiveness - Giorgi, Simona (Journal of Management Studies, 2017)
This article synthesizes the large and burgeoning literature on framing to unpack how frames achieve resonance with an audience. The analysis identifies two main resonance types: cognitive , based on an appeal to audiences’ beliefs and understandings, and emotional , based on an appeal to audiences’ feelings, passions, and aspirations. For each type, this paper delves into distinct mechanisms, applications, and outcomes to shed light on the complex bases for audiences’ reactions to framing and the factors that can hinder or favour resonance. Applications for this conceptualization of resonance and future venues of research are identified and discussed.